2000
DOI: 10.1136/jnnp.69.3.302
|View full text |Cite
|
Sign up to set email alerts
|

Strength and physiological response to exercise in patients with chronic fatigue syndrome

Abstract: Objective-To measure strength, aerobic exercise capacity and eYciency, and functional incapacity in patients with chronic fatigue syndrome (CFS) who do not have a current psychiatric disorder. Methods-Sixty six patients with CFS without a current psychiatric disorder, 30 healthy but sedentary controls, and 15 patients with a current major depressive disorder were recruited into the study. Exercise capacity and eYciency were assessed by monitoring peak and submaximal oxygen uptake, heart rate, blood lactate, du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
100
0
3

Year Published

2002
2002
2016
2016

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 144 publications
(116 citation statements)
references
References 36 publications
(38 reference statements)
12
100
0
3
Order By: Relevance
“…18 In particular, an enhanced activity of oxidative stress has been demonstrated in resting CFS patients and post-exercise. [18][19][20] Thus, impairment of mitochondrial oxidative phosphorylation and antioxidant defences have been implicated in the pathogenesis of CFS. 18;21 In the current study, differences were observed in the expression of HSP27 by CFS patients compared with control subjects, both in basal expression and following strenuous exercise.…”
Section: Discussionmentioning
confidence: 99%
“…18 In particular, an enhanced activity of oxidative stress has been demonstrated in resting CFS patients and post-exercise. [18][19][20] Thus, impairment of mitochondrial oxidative phosphorylation and antioxidant defences have been implicated in the pathogenesis of CFS. 18;21 In the current study, differences were observed in the expression of HSP27 by CFS patients compared with control subjects, both in basal expression and following strenuous exercise.…”
Section: Discussionmentioning
confidence: 99%
“…Both deconditioning and central factors have been used to explain this muscular weakness in CFS [23][24].…”
Section: Discussionmentioning
confidence: 99%
“…Patients' perceptions and expectations related to symptom exacerbation as a consequence of exercise can explain the reduced levels of physical activity found in these patients [6]. At the same time, lack of physical activity and excessive resting are factors that can result in physical deconditioning which, in turn, might perpetuate fatigue and physical disability [19]. The importance of identifying and understanding the specific cognitive and behavioral determinants of CFS is reinforced by the promising results of CBT and graded exercise approaches in CFS management [20,21].…”
Section: Introductionmentioning
confidence: 99%